2018
DOI: 10.1136/vr.104479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an intraoperative infusion of amino acids on body temperature, serum biochemistry, serum insulin and recovery variables in healthy dogs undergoing ovariohysterectomy

Abstract: Change in body temperature (BT), serum biochemistry and recovery variables were compared after infusion of amino acids (AA) or lactated Ringer's solution (LRS) in dogs undergoing ovariohysterectomy. Dogs received eight parts 10 per cent AA and two parts LRS (AA, n=10) or only LRS (CG, n=10) at 10 ml/kg/hour during 90 minutes of anaesthesia. BT was measured during anaesthesia and 60 minutes of recovery. Extubation time and shivering were noted. Serum samples were obtained before anaesthesia (T0), end of anaesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Clark‐Price and others 16 demonstrated that body temperature was better preserved and recovery parameters were improved when compared to the control group. Dogs in the treatment group maintained their body temperature for longer after induction of anaesthesia (60 v 45 min) and a significant rise in temperature was achieved sooner in recovery (40 v 50 min).…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…Clark‐Price and others 16 demonstrated that body temperature was better preserved and recovery parameters were improved when compared to the control group. Dogs in the treatment group maintained their body temperature for longer after induction of anaesthesia (60 v 45 min) and a significant rise in temperature was achieved sooner in recovery (40 v 50 min).…”
mentioning
confidence: 90%
“…A study by Clark-Price and others, summarised on p 191 of this week's issue of Vet Record, sought to address this by investigating the efect of a perioperative infusion of amino acids on the body temperature of dogs undergoing ovariohysterectomy. 16 Clark-Price and others 16 demonstrated that body temperature was better preserved and recovery parameters were improved when compared to the control group. Dogs in the treatment group maintained their body temperature for longer ater induction of anaesthesia (60 v 45 min) and a signiicant rise in temperature was achieved sooner in recovery (40 v 50 min).…”
mentioning
confidence: 96%
See 3 more Smart Citations